Models, algorithms, and heuristics for multiobjective commercial territory design - Salazar Aguilar, María Angélica (2010)
In general, distribution ﬁrms have complex product distribution networks which are formed by thousands of sales points. In this kind of industry there are many interesting problems from the logistic point of view that can appear in different stages of the decision process. For instance, when a ﬁrm is starting, a ﬁrst problem could be the facility location: where to install the warehouses and/or distribution centers. After that, in order to provide efﬁcient service and to reduce total costs (i.e., production, stock and distribution costs) some questions such as how many products need to be produced, and how to deliver the products to the ﬁnal customer, need to be answered.